2019
DOI: 10.32800/amz.2019.17.0209
|View full text |Cite
|
Sign up to set email alerts
|

mtDNA confirms the presence of Moschus leucogaster (Ruminantia, Moschidae) in Gaurishankar Conservation Area, Nepal

Abstract: Musk deer (genus Moschus), an endangered mammal, is not only of great concern for its conservation, but it is also of great interest to understand its taxonomic and phylogenetic associations in Nepal. The aim of this study was to identify the taxonomic status of musk deer in Gaurishankar Conservation Area (GCA) using mitochondrial genomic data of cytochrome b (370 bps) through phylogenetic analysis of all the species of musk deer. The results showed that the species found in GCA is confirmed as Himalayan musk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The Kashmir musk deer has historically been reported and described from the Kashmir region of the Western Himalayas from elevations between 2000 and 4200 asl [4,26,27] although some recent reports of presence of isolated populations from Nuristan, northeast Afghanistan [25], which is the western limit of the species and genetic analysis based on a few tissue samples [28] and species distribution modeling study [29][30][31], have indicated the occurrence of Kashmir musk deer in the Mustang area of central Nepal, which forms the eastern limit of the species. However, the reported occurrence of the species beyond the Kashmir Himalayas may not be true and warrants detailed investigation.…”
Section: Kashmir Musk Deer (M Cupreus Grubb 1982)mentioning
confidence: 99%
See 3 more Smart Citations
“…The Kashmir musk deer has historically been reported and described from the Kashmir region of the Western Himalayas from elevations between 2000 and 4200 asl [4,26,27] although some recent reports of presence of isolated populations from Nuristan, northeast Afghanistan [25], which is the western limit of the species and genetic analysis based on a few tissue samples [28] and species distribution modeling study [29][30][31], have indicated the occurrence of Kashmir musk deer in the Mustang area of central Nepal, which forms the eastern limit of the species. However, the reported occurrence of the species beyond the Kashmir Himalayas may not be true and warrants detailed investigation.…”
Section: Kashmir Musk Deer (M Cupreus Grubb 1982)mentioning
confidence: 99%
“…The Himalayan Musk deer were once continuously distributed all along the southern side of the Greater Himalaya in India from Central Kashmir through Himachal Pradesh up to Sikkim, Bhutan, Nepal, and marginally in China, between 3000 and 4300 m and tree line [26,35,36]. However, as a result of human habitations, habitat alterations, and poaching, they are now restricted to a few isolated pockets throughout its former range [30,33,35,37]. In Jammu and Kashmir, the Himalayan musk deer shares range and habitats with Kashmir musk deer in some of its range areas in Kishtwar NP and Bani WLS bordering Himachal Pradesh.…”
Section: Himalayan Musk Deer (M Leucogaster Hodgson 1839)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely distributed in Nepal across the Himalayan region, with a potential habitat of 5815.08 Km 2 inside protected areas (Aryal & Subedi, 2011). Himalayan musk deer are found in the Api Nampa Conservation Area (ANCA), Khaptad National Park (KNP), Annapurna Conser-vation Area (ACA), Kanchenjunga Conservation Area (KCA), Sagarmatha National Park (SNP), Langtang National Park (LNP), Gaurishankar Conservation Area (GCA), Shey Phoksundo National Park (SPNP), and Makalu Barun National Park (MBNP) and Manaslu Conservation Area (MCA) (Aryal et al, 2010;Aryal & Subedi, 2011;Shrestha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%